Effects of bicarbonate ingestion and high intensity exercise on lactate and H+-ion distribution in different blood compartments - Zinner, C.; Wahl, P.; Achtzehn, S.; Sperlich, B.; Mester, J. (European Journal of Applied Physiology, 2011)
Lactate (La) and H+-ions are unequally distributed in the blood between plasma and red blood cells (RBCs). To our knowledge there is no data concerning the effects of an oral ingestion of bicarbonate (HCO3 -) on repeated high intensity sprint exercise and La and H+ distribution between plasma and RBCs. Since an oral ingestion of HCO3 - leads to a higher efflux of La from the working skeletal muscle to the plasma, as it was shown by previous studies, this would lead to a higher gradient of La between plasma and RBCs. Although a higher gradient leads to a higher uptake, it is even more difficult for the RBCs to take up La fast enough, due to the more stressed transport system. Since RBCs function to transport La from the working muscle and help to maintain a concentration difference between plasma and muscle, this potentially increases performance during repeated sprint exercise (e.g. 4 × 30 s). The major goal of the present investigation was to test this hypothesis. 11 male participants ingested either a solution of sodium bicarbonate (NaHCO3) or placebo (CaCO3). Thereafter all performed four maximal 30 s sprints with 5 min of passive rest. During the resting periods concentrations of HCO3 -, La and H+ where measured in both blood compartments (plasma and RBCs). There were no significant differences in the La-ratios between plasma and RBCs between both interventions. These results indicate that the La/H+ co-transport is not affected by an oral ingestion on NaHCO3.